Haidt, J. (2014). Prawy umysł. Dlaczego dobrych ludzi dzieli religia i polityka? [The Righteous Mind. Why Good People Are Divided by Politics and Religion] (trans. A. Nowak-Młynikowska). Smak Słowa - Lenart, Karol (Przegląd Psychologiczny, 2023)
Abstract